TEORI RELEVANSI PADA PODCAST “SURGA HANYA UNTUK MUSLIM, NONMUSLIM APA KABAR?”: SEBUAH KAJIAN PRAGMATIK - Auliya Rahma Zain (Jurnal PENEROKA, 2025)
This research aims to analyze the harmony of speech between the speaker and the interlocutor in the podcast "Heaven is only for Muslims, non-Muslims. How are you?" based on relevance theory. This study focuses on how communication in podcasts creates optimal relevance, especially in interfaith discussions. This research uses a qualitative descriptive method with note-taking techniques. Primary data is in the form of transcripts of conversations in podcasts, while secondary data comes from supporting literature, such as books and scientific articles. Data analysis was carried out using Miles and Huberman's interactive approach, including data reduction, data presentation, and drawing conclusions. The research results show that the questions and answers in the podcast comply with the principle of relevance with a high level of efficiency, producing meaningful cognitive effects. Habib Ja'far, as the main speaker, was able to deliver relevant, direct and meaningful answers in explaining Islamic theological concepts, such as God's justice, destiny and salvation in the afterlife. These findings emphasize the importance of relevance theory in creating effective communication, especially in sensitive discussions regarding interreligious beliefs. This research contributes to pragmatic studies, especially conversation analysis based on digital media such as podcasts.